2009
DOI: 10.1590/s0100-40422009000600024
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da adsorção de compostos sulfurados empregando zeólitas contendo zinco

Abstract: Recebido em 22/7/08; aceito em 11/2/09; publicado na web em 3/7/09 STUDY OF ADSORPTION OF SULPHUR COMPOUNDS EMPLOYING ZEOLITES CONTAINING ZINC. This paper deals with an adosrption of sulphur compounds employing zeolites containing zinc. The zeolites employed were commercial NaY and Beta. The zinc was incorporated in three levels: 0.5; 1.0 and 5%. The sulphur compounds studied were benzothiophene and dibenzothiofene. The results showed that both zeolites can be employed for adsorption of benzothiophene and dibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…4 Zeolites Y and Beta have also been modified with Zn for the adsorption of benzothiophene and dibenzothiophene contaminants in cyclohexane-based model fuels. 10 Studies employing Ag + -exchanged mesopourous Al-MSU-S showed very promising results for the adsorption of thiophene and benzothiophene in n-octane. 11 Research on copper Y zeolite has suggested that the interaction with thiophene compounds occurs selectively via π-complexation.…”
Section: Introductionmentioning
confidence: 99%
“…4 Zeolites Y and Beta have also been modified with Zn for the adsorption of benzothiophene and dibenzothiophene contaminants in cyclohexane-based model fuels. 10 Studies employing Ag + -exchanged mesopourous Al-MSU-S showed very promising results for the adsorption of thiophene and benzothiophene in n-octane. 11 Research on copper Y zeolite has suggested that the interaction with thiophene compounds occurs selectively via π-complexation.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, problemas como o envenenamento de catalisadores, corrosão de equipamentos e entre outros, podem advir de compostos organosulfurados presentes na composição desse combustível fóssil (Malvesti et al, 2009).…”
Section: Introductionunclassified